ULTRASTRUCTURE OF THE CAROTID BODY - Biscoe, T. J. (The Rockefeller University Press, 1966)
An electron microscope investigation was made of the carotid body in the cat and the rabbit. In thin-walled blood vessels the endothelium was fenestrated. Larger vessels were surrounded by a layer of smooth muscle fibers. Among the numerous blood vessels lay groups of cells of two types covered by basement membranes. Aggregates of Type I cells were invested by Type II cells, though occasionally cytoplasmic extensions were covered by basement membrane only. Type I cells contained many electron-opaque cored vesicles (350 to 1900 A in diameter) resembling those in endocrine secretory cells. Type II cells covered nerve endings terminating on Type I cells and enclosed nerve fibers in much the same manner as Schwann cells. The nerve endings contained numerous microvesicles (∼500 A in diameter), mitochondria, glycogen granules, and a few electron-opaque cored vesicles. Junctions between nerve endings and Type I cells were associated with regions of increased density in both intercellular spaces and the adjoining cytoplasm. Cilia of the 9 + 0 fibril pattern were observed in Type I and Type II cells and pericytes. Nonmyelinated nerve fibers, often containing microvesicles, mitochondria, and a few electron-opaque cored vesicles (650 to 1000 A in diameter) were present in Schwann cells, many of which were situated close to blood vessels Ganglion cells near the periphery of the gland, fibrocytes, and segments of unidentified cells were also seen. It was concluded that, according to present concepts of the structure of nerve endings, those endings related to Type I cells could be efferent or afferent.